Inflammatory Myofibroblastic Tumour of the Common Bile Duct - Matilde Almeida e Sousa; Ana Carvalho; Raquel Mega; Tiago Bilhim (Acta Médica Portuguesa, 2022)
Inflammatory myofibroblastic tumour is a rare entity of indeterminate biological potential with a reduced tendency for recurrence and metastasis. Although it can arise from multiple organs, the bile duct is a very rare site of origin. We report the case of a 75-year-old asymptomatic male with elevated gamma-glutamyl transferase [1575 U/L (12 - 64 U/L)] and alkaline phosphatase [271 U/L (40 - 150 U/L)]. Computed tomography showed a 17 mm hypervascular lesion in the confluence of the right and left hepatic ducts, with bile duct ectasia and right liver lobe atrophy. The patient was initially managed as having a Klatskin tumour and underwent right hepatectomy. Histology showed a spindle cell proliferation with an inflammatory infiltrate of lymphocytes, plasma cells and collagen-rich stroma, consistent with an inflammatory myofibroblastic tumour. He was discharged 30 days after admission, and nine months later remains asymptomatic. His liver function tests have normalized and follow-up tests are unremarkable.